Development of PLA-calcium phosphate composites with high compressive strength employing a silane coupling agent (A-174) - Öner, Feyza Kevser. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2019., 2019)
Polymer-ceramic composites are being investigated in bone tissue engineering applications to obtain bone-like properties so that problems including the necessity of a second operation for metal implants are avoided. These composite materials, unfortunately, suffer from low mechanical performance compared to cortical bone and incompatible biodegradation due to low interaction between polymer and ceramic parts. In this study interaction between polymer (polylactic acid, PLA) and ceramic components (hydroxyapatite, HAP and beta-tricalcium phosphate, β-TCP) is enhanced by surface treatment of the ceramic parts using a silane coupling agent (Methacryloxypropyl trimethoxysilane, A-174). PLA-HAP and PLA-β-TCP composites were synthesized by solving casting method. The effect of ceramic surface treatment on structure, mechanical and degradation properties was investigated. Structural characterization employing FTIR, XPS, SEM and XRD was performed for raw materials and composites. It was concluded that surface treatment using silane A-174 can increase polymer dispersion on ceramic surface and improve polymer-ceramic interactions in both systems. The composite synthesized by 3% silane treated HAP and PLA in equal mass proportions (PLA50H50Si3) displayed a compressive strength value of 364 MPa, exhibiting a superior performance compared to other composites previously reported. It was observed that surface modification results in obtaining a more controlled degradation in PLA-β-TCP composites while it does not seem to influence the degradation in already stable PLA-HAP composite within the time frame the experiments were performed.
Keywords: Calcium phosphate.; Composite materials.